1994
DOI: 10.1172/jci117474
|View full text |Cite
|
Sign up to set email alerts
|

The pentraxins, C-reactive protein and serum amyloid P component, are cleared and catabolized by hepatocytes in vivo.

Abstract: The cellular sites of clearance and degradation of the pentraxin plasma proteins, C-reactive protein, the classical acute phase reactant, and serum amyloid P component (SAP), a universal constituent of amyloid deposits, were sought using the ligand 'MI-yramine cellobiose (TC) which is substantially retained within the cells in which catabolism takes place. Pentraxins labeled with '"I-TC showed the same in vitro and in vivo ligand binding and the same in vivo plasma to as the directly iodinated proteins and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
42
0
1

Year Published

1998
1998
2009
2009

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(45 citation statements)
references
References 29 publications
2
42
0
1
Order By: Relevance
“…They and other investigators further demonstrated that the bulk of circulating CRP is produced by hepatocytes largely under regulatory control of inflammatory cytokines including interleukin-6 (IL-6) and tumor necrosis factor-␣; that the plasma half-life of CRP is approximately 19 h under basal and stress conditions; and thus that the plasma concentration is largely determined by synthetic rate (14,15 ).…”
Section: C-reactive Protein (Crp)mentioning
confidence: 99%
“…They and other investigators further demonstrated that the bulk of circulating CRP is produced by hepatocytes largely under regulatory control of inflammatory cytokines including interleukin-6 (IL-6) and tumor necrosis factor-␣; that the plasma half-life of CRP is approximately 19 h under basal and stress conditions; and thus that the plasma concentration is largely determined by synthetic rate (14,15 ).…”
Section: C-reactive Protein (Crp)mentioning
confidence: 99%
“…injection into mice, compared to the Ϸ3-h plasma half-life of native human SAP in mice (26). Circulating SAP is normally cleared in vivo exclusively by hepatocytes (26) but not via the asialoglycoprotein receptor (27) and the rapid clearance of the SAP-CPHPC complex in mice was also not affected by concurrent administration of desialylated orosomucoid to block this receptor (27). Circular dichroism measurements showed no significant secondary or tertiary structural change in the SAP-CPHPC complex compared to native SAP alone (Fig.…”
mentioning
confidence: 99%
“…The plasma clearance rates of 125 I-human CRP, after i.v. injection into groups of age-matched male apoE Ϫ/Ϫ -hCRP ϩ and apoE Ϫ/Ϫ mice, were measured exactly as described (36).…”
mentioning
confidence: 99%